Strategi Koalisi Partai Keadilan Sejahtera dalam Pemenangan Pemilihan Walikota dan Wakil Walikota Pekanbaru 2010-2011 - Wazni (Nakhoda: Jurnal Ilmu Pemerintahan, 2013)
PKS has requirements that must be observed by candidates for mayor/deputy mayor to be carried include: having the support of political parties, the mass base of support and success program. Because the non-fulfillment of the quota of 15 seats in parliament, PKS makes the initial coalition with Paradise as individu. Selanjutnya, the coalition continued with the coalition parties combined. There are six parties joined-Versecarries Firdaus Cahyadi are: PKS, Hanura, UN, PDK, the Democratic Party and the PDI-P.